Design of Real-Time Project Monitoring Dashboard Using Kimball’s Data Warehouse Approach and Google Data Studio - Savitri, Ni Kadek Wiliya; Sandhiyasa, I Made Subrata; Fittryani, Yuri Prima; Sudipa, I Gede Iwan; Putra, Desak Made Dwi Utami (Sinkron : jurnal dan penelitian teknik informatika, 2025)
The growth of the construction industry in Indonesia triggers an increasing need for an efficient project management system, especially in presenting project data accurately and in real-time. PT Dream Island Development (PT DID), a specialist MEP contractor company, faces challenges in presenting project reports to executives because the data is still presented in the form of Excel tabulations which require up to three days of processing time and are difficult to interpret quickly. This research aims to design an interactive dashboard-based project data visualization system using Google Data Studio (Looker Studio) to present project information intuitively and responsively. The method used includes a software engineering approach with five main stages: requirements analysis, data warehouse design, ETL process using Pentaho Data Integration, visualization using Google Data Studio, and testing using User Acceptance Test (UAT). Project data from 2022-2024 was modeled using a star schema and displayed in four main dashboards: project cost, project value, project progress, and details per project. The test results showed a high level of user satisfaction with a functionality score of 93.5%, reliability 91.33%, usability 96%, and efficiency 94.66%. These findings indicate that the developed system effectively supports PT DID's needs in project monitoring and data-based decision-making. The system also has the potential to be replicated in other construction companies as an efficient and scalable business intelligence solution. This research contributes to the growing body of construction informatics by integrating Kimball’s nine-step methodology with modern data visualization tools to enhance project transparency and decision-making.